Ciência e a Ciência Paralela: Uma disputa do campo científico - Silva, Gabriel Moutinho Fernandes (Universidade Federal de São Carlos, 2025)
The monograph in question aims to present a case study about the recent production made by the production company Brasil Paralelo, entitled Unitopia, which produces a critique of Science and the production of scientific knowledge itself. To this end, we analyzed the two episodes of the documentary and an e-book material, with the objective of analyzing some aspects of the narrative produced, namely, the dispute of symbolic capital in which the documentary analyzes universities, since the members are part of the scientific field. In our objectives, we aim to answer our research questions: (1) Why position oneself in the Academy, even while rejecting it? and (2) What is the interest in using trivialization as a positioning tool? Aiming to highlight our hypothesis that Brasil Paralelo, as a group, seeks with its productions, in this work focusing our attention on UNITOPIA, a space for positioning within the academic world, seeking for this purpose groups with less power and that, in order to be seen, trivialize the knowledge of those who judge their adversaries. To this end, we used Pierre Bourdieu's writings and analyses on the scientific field as methodological material, enabling us to understand the positions taken by members of science. We also highlight the construction of science and its rules and structures with Robert K. Merton's notion of scientific ethos; and the analysis of the Strong program in Sociology of Knowledge, by David Bloor. We also highlight the conservative theories of James Durham and Mark R. Levin, who, even though they wrote at different times, have a vision similar to that of the narrative presented in Unitopia.
Science and Parallel Science: a struggle within the scientific field
Keywords: Ciência; Science; Campo científico; Scientific field; Brasil Paralelo; Parallel Brazil; Disputas pelo campo; Disputes over the field; CIENCIAS HUMANAS::SOCIOLOGIA